Navigating Transitions: A Psychoeducation Toolkit for First-Year Engineering Students' Academic and Social Adjustment to Hybrid Learning - Firmante, Maria Cristina M (Journal of Social and Scientific Education, 2025)
This psychoeducation toolkit was developed using an action research framework to support first-year engineering students in navigating the unique academic and social challenges of hybrid learning in the post-pandemic context. Drawing on phenomenological insights from Firmante’s (2024) study on Filipino engineering students’ transition to college in hybrid settings, the toolkit addresses difficulties such as managing academic workload, overcoming social isolation, adapting to new learning platforms, and regulating emotions in a hybrid learning environment. Grounded in action research principles, namely iterative development, participatory input, and context-specific adaptation, the toolkit integrates qualitative findings from Firmante’s study to inform the structure and content of the intervention. Six weekly modules (each 90 minutes) are designed to be delivered in both face-to-face and online formats to accommodate varied student schedules and technological access. Each session targets specific competencies: Session 1 focuses on understanding hybrid learning and its impact; Session 2 on academic adjustment and stress management; Session 3 on social integration and relationship building; Session 4 on coping with mental health challenges; Session 5 on self-advocacy and seeking help; and Session 6 on building resilience and well-being. Intended outcomes of the toolkit include improved time management skills, enhanced emotional regulation, increased peer interaction, and elevated mental health literacy. The toolkit aims to facilitate a smoother and more resilient transition to college life for first-year engineering students engaged in hybrid learning environments by providing an evidence-based, contextually grounded group psychoeducation intervention.